2020
DOI: 10.3390/en13215708
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Engine Performance, Emissions and Combustion Characteristics of Biodiesel and Its Blends Derived from Catalytic Pyrolysis of Waste Cooking Oil

Abstract: This paper first describes a slow catalytic pyrolysis process used for synthesizing biodiesel from waste cooking oil (WCO) as a feedstock. The influence of variations in the catalyst type (sodium hydroxide and potassium hydroxide), and catalyst concentration (0.5, 1.0, 3.0, 5.0, 7.0 and 10.0% by weight) on both the pyrolysis temperature range and biodiesel yield were investigated. The results suggested that sodium hydroxide (NaOH) was more effective than potassium hydroxide (KOH) as catalysts and that the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…The ignition of the fuel is not spontaneous; it is controlled by the Hardenberg and Haze model whose mathematical formulation is given by relation 14 [23][24][25]: (15) where E A is the activation energy, where, R is the universal gas constant.…”
Section: Ignition Delay Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The ignition of the fuel is not spontaneous; it is controlled by the Hardenberg and Haze model whose mathematical formulation is given by relation 14 [23][24][25]: (15) where E A is the activation energy, where, R is the universal gas constant.…”
Section: Ignition Delay Modelmentioning
confidence: 99%
“…B100 biodiesel would have better performance at high loads. This behavior is probably due to the oxygenation of the molecule and the structural simplicity of its chemical composition [23][24][25][26]30]. At high temperatures, the relatively higher viscosity of biodiesel is no longer fundamentally a handicap for the combustion of this fuel.…”
Section: Heat Release Curve For 100% Loadmentioning
confidence: 99%
“…Furthermore, there was a reduction in carbon dioxide (CO2) and nitrogen oxides (NOx). Furthermore, they discovered that 2-ethyl 1hexanol is a superior additive to pentanol since it emits less NOx, HC, and CO. (Mohamed, Tan et al 2020), explored the releases, Performance, and characteristics combustion of a biodiesel engine and its mixtures made from catalytic pyrolysis of waste vegetable oils in an experimental setting. The impacts of various catalyst types (sodium hydroxide vs. potassium hydroxide) have also been researched.…”
Section: Introductionmentioning
confidence: 99%
“…Raheman and Phadatare [13] found a CO emission reduction of about 73-94% for Karanja Methyl Ester (B100) and its mixtures (B20, B40, B60, and B80) when compared with diesel fuel. Mohamed et al [14] reported that average HC emission reductions from the biodiesel fuel blends were only observed for blend ratios no higher than 40% for five different types of biodiesel compared with pure diesel fuel. Kale et al [15] proposed that microalgae biodiesel and its various diesel blends will be used as promising alternative fuels for diesel engines due to their advantages.…”
Section: Introductionmentioning
confidence: 99%